Mandatory Bequest (Wasiat Wajibah) in Interfaith Inheritance Cases (A Study of Indonesian Supreme Court Decision No. 16 K/AG/2010 from the Perspective of Maqāṣid al-Sharī‘ah) - Muhammad Baihaqi (QURU’: Journal of Family Law and Culture, 2026)
A person’s death often gives rise to inheritance disputes, especially when there is a difference of religion between the deceased (the decedent) and the heirs. In Islamic law, the majority of jurists hold that a difference of religion constitutes an impediment to mutual inheritance. Nevertheless, some scholars propose an alternative solution through the mechanism of wasiat wajibah (mandatory bequest) for parties who are legally barred from inheriting. Building on this reality, this study aims to analyze the legal reasoning in the decisions at the first instance, appellate, and cassation levels by using the perspective of Maqāṣid al-Sharī‘ah, in order to assess the extent to which those decisions reflect principles of justice and public benefit (maṣlaḥah). This research is a library-based study with a descriptive-analytical character. The approaches employed include normative juridical and statutory juridical approaches, while remaining grounded in the overarching objectives of Islamic law (Maqāṣid al-Sharī‘ah). The findings indicate that Indonesian Supreme Court Decision No. 16 K/AG/2010 expands the application of wasiat wajibah which, under the Compilation of Islamic Law (KHI), is originally intended only for adopted children and adoptive parents into a solution for contemporary inheritance problems, including for non-Muslim heirs. Through this decision, the Supreme Court determined that parties who are barred from inheriting due to religious difference may still receive a portion of the estate through a mandatory bequest, based on considerations of justice, humanity, and social welfare. This decision is considered consistent with the objectives of Islamic law, particularly the protection of religion, life, and property, because it preserves the core principles of Islamic inheritance law while also providing protection and welfare for those otherwise excluded. The implementation of wasiat wajibah is relevant to Indonesia’s plural society and reflects the orientation of Islamic law toward the public good (maṣlaḥah) of the community. This article recommends: clarifying the regulation of wasiat wajibah in the Compilation of Islamic Law (KHI) including for heirs of different religions; issuing Supreme Court (MA) technical guidelines to ensure consistent and predictable rulings; and strengthening legal literacy/mediation as well as inheritance planning (wills and hibah) to prevent disputes in line with maqāṣid al-sharī‘ah.